Analyse the Development of NFT Art from the Perspective of Audience Psychology - Cheng, Shengjie (Transactions on Social Science, Education and Humanities Research, 2024)
With the rapid development of blockchain technology, non-homogenized tokens (NFT) have gradually become a new favorite in the field of digital art. NFT gives the artwork a unique symbol, so that each piece of work can be accurately identified and certified. At the intersection of contemporary art and technology, NFT art has gradually developed into a force. Its rise is not accidental, but the result of various factors. However, the progress of technology does not mean that the development of art can be left alone. NFT art faces many challenges in its development process, the most important of which is the acceptance of the audience. This paper tries to use the development of NFT art and explore the theory of audience psychology from the perspective of audience psychology, analyze the psychosocial motivation behind it, and give the corresponding perspective.